The Impact of a Tiered Network on Hospital Choice - Frank, Matthew B (Health Serv Res, 2015)
OBJECTIVE: To evaluate the effect of a tiered network on hospital choice for scheduled admissions. DATA: The 2009–2012 patient-level claims data from Blue Cross Blue Shield of Massachusetts (BCBSMA). STUDY DESIGN: BCBSMA's three-tiered hospital network employs large differential cost sharing to encourage patients to seek care at hospitals on the preferred tier. During the study period, 44 percent of hospitals were moved to a different tier based on changes in cost or quality performance. We relied on this longitudinal variation for identification and specified conditional logit models to estimate the effect of the tiered network (TN) on patients' hospital choices relative to a non-TN comparison group. PRINCIPAL FINDINGS: The TN was associated with increased use of hospitals on the preferred and middle tiers relative to the nonpreferred tier for planned admissions. The results suggest that if all members were in a TN plan, relative to all members being in a non-TN plan, scheduled admissions to hospitals on the nonpreferred tier would drop by 7.6 percentage points, while those to middle and preferred tier hospitals would rise by 0.9 and 6.6 percentage points, respectively. CONCLUSION: Differential cost sharing can steer patients toward preferred hospitals for planned admissions.